2018
DOI: 10.3390/w10040506
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Rainwater Harvesting in Malaysia: Prospects and Challenges

Abstract: The mismatch between freshwater demand and its availability is a major problem that causes global water scarcity. The exploration and utilization of rainwater seem to be viable options for minimizing the aforementioned issue. This manuscript reviews the prospects and challenges of the rainwater harvesting system (RWHS) in Malaysia. Malaysia can be categorized as a country that has high annual rainfall, as well as high domestic water consumption. Thus, Malaysia is well positioned to harvest rainwater for both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 111 publications
(130 reference statements)
1
42
0
1
Order By: Relevance
“…When looking for alternative sources of water, special attention was paid to rainwater, which usually is characterized by a low degree of pollution, which does not require advanced cleaning processes [12][13][14]. This applies mainly to rainwater coming from areas located far from city centers and industrial plants, from which anthropogenic pollution emitted to the atmosphere can significantly affect the quality of atmospheric precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…When looking for alternative sources of water, special attention was paid to rainwater, which usually is characterized by a low degree of pollution, which does not require advanced cleaning processes [12][13][14]. This applies mainly to rainwater coming from areas located far from city centers and industrial plants, from which anthropogenic pollution emitted to the atmosphere can significantly affect the quality of atmospheric precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, water scarcity has become a global issue due to high water demand and depleting water availability [1]. Population growth, urbanization and industrialization have exerted tremendous pressures on water resources [2]. Furthermore, climate change has also exacerbated the decrease of water resources in many parts of the world, including the Mediterranean basin, Western United States and Southern Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aims of this review paper are: (1) to review the types of RWHS design, its component and current performance in terms of rainwater quantity and quality as well as energy consumption; (2) to highlight the benefits and challenges in environmental, economic and social aspect of the RWHS application; and (3) to suggest the way forward in RWHS implementation and to identify the future potentials for PHS application.…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent studies which have been carried out on the rainwater quality in Malaysia, RWH has the potential to reduce cost and the usage of treated water as well as can be considered as one of the alternative for the water resources [8,9]. Although RWH is gaining much interest, the implementation has been limited due to several disadvantages such as seasonal variation and related cost [7,[10][11][12][13]. Recently, Hafizi Md Lani et al [13] concluded that Malaysia is well positioned to harvest rainwater and to be a saviour for the water shortage, but in some places or event, it cannot completely dependable source of water supply due to uneven rainfall distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Although RWH is gaining much interest, the implementation has been limited due to several disadvantages such as seasonal variation and related cost [7,[10][11][12][13]. Recently, Hafizi Md Lani et al [13] concluded that Malaysia is well positioned to harvest rainwater and to be a saviour for the water shortage, but in some places or event, it cannot completely dependable source of water supply due to uneven rainfall distributions. As to support the RWH system, other natural resources can be considered.…”
Section: Introductionmentioning
confidence: 99%